THE APPLICATION OF LANDSAT TM DATA AND SRTM DATA FOR DETECTION VULNERABILITY ASSESSMENT OF FLOOD IN BENGAWAN SOLO WATERSHED - RAHARJO, P.D.; LAROSA, T.F. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
Bengawan Solo watershed is one of watershed that has frequent floods. Due to high rainfall in the rainy season, the river can?t accommodate the surface runoff and resulted flooding around the area. The high rainfall is not only causing flood in some areas upstream watershed, but also threaten the downstream areas in East Java province, especially Bojonegoro, Lamongan, Tuban and Gresik. Data of remote sensing and Geographic Information System (GIS) could detect assessment vulnerability of flooding. The research objective is to study flood vulnerability assessment in Bengawan Solo watershed using remote sensing data. The method is the combination of information from remote sensing data, i.e.. (1) to combine band 4 with band 7 Landsat TM in which the flood pixel value is ? 78; (2) to detect flow accumulation using SRTM data; and (3) to detect flooding areas at the altitude of 0-50 m. The result obtained from the study is the flood vulnerability in Bengawan Solo watershed including Sragen District (Masaran, Plupuh, Gesi, Sidoharjo Sub District); Ngawi (Widodaren, Kedungalar, Pitu SubDistrict); Tuban District (Rengel, Plumpang, Widang Sub District); Bojonegoro (Padangan, Malo, Kalitidu, Trucuk, Bojonegoro,Dander, Kanor, Baureno, Sumberejo Sub District); Lamongan (Laren, Solokuro, Karanggeneng, Kalitengah Sub District); Gresik Regency (Hamlet and Bungah Sub District).